Scratching beneath the surface while coupling atmosphere, ocean and waves: Analysis of a dense water formation event. (May 2016) - Carniel, Sandro; Benetazzo, Alvise; Bonaldo, Davide; Falcieri, Francesco M.; Miglietta, Mario Marcello; Ricchi, Antonio; Sclavo, Mauro
Highlights: An exceptional cold spell stroke the northern Adriatic sea during winter 2012. We describe the event using a fully coupled ocean-atmosphere-wave modeling approach. Atmosphere-coupled ocean produces improved heat fluxes and air temperatures estimates. Model coupling improves dense water properties and dynamics description. Implications of coupling affect density and kinetic energy of the whole basin. Abstract: Cold Air Outbreaks (CAOs) over shallow seas may lead to dense water formation episodes, enhancing water, heat, nutrient and sediment exchanges across the continental margin, with associated seabed reshaping. During winter 2012, a CAO episode characterised by exceptional intensity stroke the northern Adriatic Sea, one of the most effective cool engines driving the Mediterranean circulation, providing a paramount opportunity for an integrated investigation of dense shelf water dynamics. In the present study, we describe this event using a fully coupled modeling approach exploring the effects of mutual interactions among atmosphere, ocean currents and sea surface waves, usually not completely accounted for, in the resulting dense water formation. Whilst atmospheric fields appear to be marginally affected by coupled dynamics in the present case, implications for sea surface elevation and circulation are far from negligible. Measurements collected in the northern Adriatic Sea showed that a physically consistent description of energy exchanges between ocean and atmosphere provides an improved estimate of heat fluxes and of air and sea temperatures. In addition, the explicit inclusion of wave action within the modeling system further enhances the modulation of air-sea exchanges and the propagation of its effect along the water column, resulting in a different intensity of northern Adriatic gyres and in different water fluxes flowing through the formation basin. Through these main controls on the water volume involved in the densification process and on the intensity of momentum input and cooling, a coupled modeling strategy accounting for atmosphere-waves-currents interactions can turn out to be crucial for improving the quantification of thermohaline properties and energy content, newly formed dense water mass, and provide a better description of its migration pathways and rates of off-shelf descent.